FRI0198 OCULAR MORBIDITY IN PATIENTS WITH PMR AND GCA IN THE UK - A CPRD STUDY. (2nd June 2020) - Yates, M.; Clark, A.; Watts, R.; Macgregor, A.; Mackie, S.
Abstract : Background: Visual loss is the most serious consequences of a diagnosis of polymyalgia rheumatic (PMR) and giant cell arteritis (GCA). To date, information on the occurrence of eye disease in GCA has been based almost exclusively on small hospital-based patient series. Furthermore the lack of control group for these studies results in a lack of relative risk estimates for visual loss. There are no accurate data on the prevalence and nature of eye complications among patients in the community. Patients with GCA may be exclusively managed in the primary care setting without referral for either temporal artery biopsy or ophthalmic department examination. Currently the incidence and prevalence of eye complications within this group are unknown. Objectives: Examine the absolute rate and relative risk of ocular morbidity, in a longitudinal community setting, in patients with PMR and or GCA including visual loss, AOIN including optic atrophy, cataract and glaucoma identified from Read codes in the (Clinical Practice Research Datalink) CPRD dataset. Methods: Construction of a disease cohort of incident diagnoses of PMR and GCA from patients in the CPRD matched to controls on age, sex (+/- 2 years) and practice location. Diagnosis were identified by CPRD researchers of those individuals between January 1997 to December 2015, with a minimum age at diagnosis of 50 years. Those with both a diagnosis of PMR and GCA were analysed in the GCA group. The outcomes of ocular morbidity included Read codes for severe visual impairment (multiple codes covered: blindness, severe visual impairment, registered partially sighted, issue of certificate of visual impairment, examination findings of 4/60 or worse), anterior ischaemic optic neuropathy (including codes of optic neuropathy and atrophy but not codes of glaucomatous atrophy), cataract, cataract extraction and glaucoma. Statistically modelling with Cox proportional hazards was used to generate hazard ratios for ocular morbidity taking account of censorship through death and moving out of area. Results: We identified 30, 714 individuals with PMR (20, 270 women; 66%) with a mean age at diagnosis of 72.9 year (sd 9.1) and 6, 104 with GCA (4, 309 women; 70.6%) with a mean age of 72.1 years (sd 9.4). Of those diagnosed with GCA 1, 669 were also diagnosed with PMR. Using Read codes for severe visual impairment and blindness 5.9% of patients with GCA and 2.7% with PMR had this complication compared with 1.6% of the matched controls. The hazard ratio for the various ocular morbidities and by cases of PMR or GCA are shown in the table below: Conclusion: These community-based national data on risk of ocular morbidity in PMR and GCA show for the first time the risk of various ocular morbidities are increased for both groups. In addition this are the first estimates of relative risk compared to an age and sex matched population. These data are crucial for providing information to patients about their relative risk of ocular morbidity following a diagnosis of PMR or GCA. Acknowledgments: We would like to thank Dr Helen Strongman at the CPRD for carrying out patient searchers. We thank Dr Ferran Espuny Pujol for completion of the linkage request for dates of death. Disclosure of Interests: Max Yates: None declared, Allan Clark: None declared, Richard Watts: None declared, Alex MacGregor: None declared, Sarah Mackie Grant/research support from: Roche (attendance of EULAR 2019; co-applicant on research grant), Consultant of: Sanofi, Roche/Chugai (monies paid to my institution not to me)